Centenary of a Serendipitous Inventor: Stookey and a Short Statistical Overview of Photosensitive Glass & Glass-Ceramics Science and Technology - L.F. Nascimento, Marcio (Recent Patents on Materials Science, 2016)
In this short statistical report, we compile and analyze statistics on past and current scientific and technological research on photosensitive glass (PG) as well as glass-ceramics (GC). Their developments have traced remarkable histories since their first commercial discoveries in the 1940s and 1950s, both the work of Don Stookey. These products and processes have transformed modern life and are two of the most widely reported methods for special glass manufacturing. They provide security, are of high quality mass production. The U.S., Japan and China have been leaders in PG glass development, the second place going to China in terms of GC research communities. We have observed very significant progress in recent decades with an exponential growth in the number of scientific publications and patents for PGs and GCs due to new publications, author keywords, affiliations and primary characterization techniques. More than 6,497 patents were filed globally prior to 2015 with the terms “photosensitive and glass” and 9,738 with the terms “glass and ceramics” within the title or abstract according to the European Patent Office. These numbers have continued to grow along with worldwide PG and GC-related sales. Based on the Scopus database, for the same period 1,405 PG documents and 30,819 GC-related (primarily manuscripts) were published with the same terms in the title, abstract or keywords list. From this statistical analysis, both PG and GC will continue to be fascinating materials for further research, development and uses in the near future.
Keywords: Glass